Acoustics of the West Kennet Long Barrow, Avebury, Wiltshire. (2nd January 2016) - Marshall, Steve
ABSTRACT: Continuing on from a 2011 preliminary study, this paper investigates further the acoustical properties of one of Wiltshire's best-known monuments, the West Kennet long barrow, in the Avebury complex. Its two pairs of transepted chambers resonate at frequencies that are musically a 'perfect fourth' apart – a ratio of 4:3. The frequency of the resonances is dictated by the size of the chambers, which in plan are also proportioned 4:3. Several other Cotswold-Severn tombs contain chambers with this 4:3 ratio. Furthermore, the central passage of West Kennet resonates at an extremely low frequency that can produce certain psychological effects; other Neolithic tombs are similarly-proportioned. It is possible that these effects were employed for some ritual purpose in West Kennet and other monuments.